Maternal Preconception Stress Alters Prefrontal Cortex Development in Long–Evans Rat Pups without Changing Maternal Care. (1st December 2018) - Jenkins, Serena; Harker, Allonna; Gibb, Robbin
Highlights: Dams exposed to preconception stress show the same level maternal care as control dams. The effects of maternal preconception stress on the prefrontal cortex are sex- and region-dependent. Maternal preconception stress does not affect the development of sensorimotor and locomotor activity in offspring. Our results may suggest that maternal preconception stress provides an adaptive mechanism for dealing with early stress. Abstract: Stress during development can shift the typical developmental trajectory. Maternal stress prior to conception has recently been shown to exert similar influences on the offspring. The present study questioned if a consistent maternal stressor prior to conception (elevated platform stress) would impact the pre-weaning development of offspring brain and behavior, and if maternal care was vulnerable to this experience. Adult female Long–Evans rats were subjected to elevated platform stress for 27 days prior to mating with non-stressed males. Maternal care was monitored, and pups were assessed in two tests of early behavioral development, negative geotaxis and open field. Pups were perfused at weaning and their brains were extracted and stained with Cresyl Violet, allowing gross measurements of cortical and subcortical structures and estimates of neuron density. Main findings indicate that a change in prefrontal cortical thickness is evident despite no change in maternal care. Female offspring show a decrease in medial-dorsal thalamus size. The current study failed to find an effect of maternal preconception stress on early behavioral development. These results suggest that the PFC, and likely behavior dependent on the PFC, is vulnerable to maternal preconception stress and that a strong sex effect is evident. Further studies should examine how such offspring fare using a lifespan model and investigate potential mechanisms responsible for these effects.